Menelaah Peran Pria dalam Penggunaan Kontrasepsi Hormonal: Upaya Mencapai Kesetaraan Gender dalam Pengaturan Reproduksi - Ni Made Mirah Candrawati; Ni Putu Dewi Sri Wahyuni; Pande Bagus Andhika Maharthanegara; Ni Kadek Indah Melati; Tjokorda Prawira Putra Pemayun; Komang Nirartha Nusaryanda (Pusat Riset dan Inovasi Nasional, 2026)
Contraceptive use remains predominantly female-driven, encompassing both hormonal and non-hormonal methods. This situation reflects a gender imbalance in reproductive responsibility, which should ideally be a shared role between men and women. In fact, male involvement holds significant potential to alleviate the reproductive burden on women and strengthen gender equality efforts. This study is a systematic review conducted according to the PRISMA protocol and PICO framework, analyzing literature from PubMed, ScienceDirect, and Google Scholar (2018–2025) to evaluate men’s knowledge, acceptance, and participation in contraception. Various male contraceptive methods are currently available, such as condoms and vasectomy, alongside emerging innovations including testosterone-progestin-based hormonal methods and non-hormonal options like RISUG®, Vasalgel™, and BRDT inhibitors. Despite promising efficacy, the utilization of male contraception remains low due to socio-cultural factors, stigma, and a lack of knowledge regarding available options. Furthermore, gender-based policy support and education remain limited. Educational approaches, involving men in family planning services, and interdisciplinary research integrating molecular biology, genetics, and wearable technology have the potential to yield safer, reversible, and socially acceptable contraceptive methods. Male engagement in contraception is key to achieving gender equality in reproductive health. Efforts to increase male participation must be implemented comprehensively through education, gender-equitable policies, and innovative research support to develop effective and widely accepted male contraceptives.